Digital Fire and Salvage Unit: A New Level of Training for Emercom Cadets - Igor A. Malyj; Vladislav V. Bulgakov; Irina Yu. Sharabanova (Открытое образование (Москва))
The purpose of the study. The purpose of the work is to substantiate and develop software for the organization, management and control of the educational process, including the form of practices and internships, in the educational fire and salvage unit of the departmental university of EMERCOM. The relevance and the need for automation of the educational process is connected with the need to improve the training process for both cadets on practical training programs and permanent personnel of the fire and rescue training unit for service and professional training. The practical training of cadets currently being implemented on the basis of the fire and rescue training unit has a time-limited training format, in the form of a day on duty in three days, which does not allow without the widespread use of digital technologies to increase the level of organization of the educational process and its effectiveness, for example, by ensuring constant access of trainees to educational materials.Materials and methods. To develop a technical assignment for the creation of software, methods of scientific and pedagogical research were used, containing the analysis and synthesis of information, including both the practice of organizing the educational process in the educational fire and salvage units of universities of EMERCOM, and the requirements of regulatory legal documents for the official and professional training of firefighters. A review of software products was carried out, the possibility of their application for the organization and conduct of practices and internships of trainees of EMERCOM was evaluated, the requirements for the functionality of the software and the procedure for its use in the training fire and salvage unit were formulated.Results. The software “Digital Fire and Salvage Unit” has been developed, which has been introduced into the educational and practical activities of the departmental university of EMERCOM. The software is implemented in the form of a website (http://dfs edufire37.ru), which is supported by all modern types of browsers and adapted for mobile devices. The program includes 12 main functional modules that allow you to organize the administration and management of users, develop methodological and control and measuring materials, form a practice program or training program, a schedule of training sessions, a knowledge base and an electronic journal, receive information about the results of training, organize a game form of training through intellectual duels between users, as well as access to information about the available training fire and salvage unit of fire equipment, fire-technical and rescue equipment, to an interactive map of the area of departure of the fire-rescue guard with the placement of various objects of protection and their characteristics, roads, water sources and other information necessary for the elimination of fires. In addition, the program provides a functional module “Forum” and “Personal messages”, designed for discussion between users of topical issues of training and professional activity.Conclusion. The paper substantiates the need to introduce digital educational technologies into the activities of the educational fire and salvage unit of the University of EMERCOM to improve the efficiency of the organization, management and control of practices and internships of cadets. The presented software ensures the performance of functional tasks both in the field of training cadets at the University of EMERCOM, and in the field of service and professional training of the permanent staff of the training fire and salvage unit. A promising direction is the introduction of the presented software into the activities of practical fire and salvage units for the organization of service and professional training of firefighters.